2003
DOI: 10.1159/000074052
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Rheumatoid Arthritis in Kuwaiti Patients in an Outpatient Hospital-Based Practice

Abstract: Objective: To describe the characteristic clinical, serologic and radiological features of rheumatoid arthritis (RA) in Kuwaiti patients in a tertiary outpatient hospital-based practice. Subjects and Methods: An outpatient hospital-based study on 100 consecutive consenting Kuwaiti patients with RA was done at the Rheumatology Unit, Al-Amiri Hospital, one of the main teaching hospitals in Kuwait. The study group included 11 men and 89 women. The duration of their disease ranged from 2 to 30 years with a mean du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…Our study showed that the majority of patients was female (67%) and they were more frequently Qataris (91.3%) compared with Asians (52.5%) which reflects the pattern of the Qatar population (most Asians are male). Among all patients, RF was positive in 63%, anti‐CCP in 71% and both were positive in 49% which is close to that reported from Kuwait 60% . A comparative study of RA in British and Malaysian patients showed that RF was positive in 65% in each group of patients which is similar to our study …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study showed that the majority of patients was female (67%) and they were more frequently Qataris (91.3%) compared with Asians (52.5%) which reflects the pattern of the Qatar population (most Asians are male). Among all patients, RF was positive in 63%, anti‐CCP in 71% and both were positive in 49% which is close to that reported from Kuwait 60% . A comparative study of RA in British and Malaysian patients showed that RF was positive in 65% in each group of patients which is similar to our study …”
Section: Discussionsupporting
confidence: 88%
“…Few studies have reported prevalence and characteristics of the disease in an Arab population. Studies from Iraq, Kingdom of Saudi Arabia, Kuwait and Lebanon have suggested RA in Arab patients to be mild and nondestructive. These studies were descriptive and did not include disease activity score (DAS) measurement, However.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of estrogen was mediated by estrogen receptors located in the multiple immune cells (T cells, B cells, monocytes, and macrophages) as well as in the thymus [ 53 ]. This effect can be achieved by directly manipulating the profile of T-helper cytokine from interleukin (IL)-2, TNF - α , and interferon (IFN)- γ (pro-inflammatory) to IL-4, IL-6, and IL-10, transforming growth factor (TGF)- β (anti-inflammatory) direction [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two small hospital studies in Saudi Arabia also showed that radiographic changes in the hands and feet of RA patients were less severe, and the proportion of patients with erosions (60%) was lower than those reported in Western European and North American studies . Similarly, a study in 100 consecutive RA patients in Kuwait found a low incidence (42%) of radiological erosive arthropathy, with sicca complex being the most common extra‐articular manifestation of RA …”
Section: Challenges In the Optimal Management Of Ra In Africa And Thementioning
confidence: 92%
“…In addition, the management practices also vary, in accordance with the healthcare infrastructure and socioeconomic status of patients. Of note, most countries do not have their own consensus guidelines for RA management …”
Section: Challenges In the Optimal Management Of Ra In Africa And Thementioning
confidence: 99%